2003
DOI: 10.1002/jmr.629
|View full text |Cite
|
Sign up to set email alerts
|

Calix[8]arene‐mediated self‐assembly of tetrapeptide H‐Leu‐Leu‐Ile‐Leu‐OMe

Abstract: Conformational analysis of peptide 1, H-Leu-Leu-Ile-Leu-OMe on complexing with macro cycle calix[8]arene has been carried out using (1)H-NMR and FTIR spectroscopic techniques. Stoichiometry of the complex formed in the 1:8 ratio was evidenced by a Job plot. NMR studies of the above peptide show a marked downfield shift and an increase in (3)J values for NH resonances on complexing with calix[8]arene. The characteristic NOE connectivity between N(i+1)H and C(ialpha)H confirm beta-sheet conformation in the compl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…It is known that the resonances of hydrogen‐bonded protons are shifted downfield relative to protons that are not involved in hydrogen bonds, thereby indicating that they are deshielded due to their participation in the hydrogen bonding 37. A study on proton NMR spectroscopic shifts of these complexes indicated that CH⋅⋅⋅N and amide hydrogen bonds also occur in solution in non‐coordinating solvents (CDCl 3 and C 6 D 6 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is known that the resonances of hydrogen‐bonded protons are shifted downfield relative to protons that are not involved in hydrogen bonds, thereby indicating that they are deshielded due to their participation in the hydrogen bonding 37. A study on proton NMR spectroscopic shifts of these complexes indicated that CH⋅⋅⋅N and amide hydrogen bonds also occur in solution in non‐coordinating solvents (CDCl 3 and C 6 D 6 ).…”
Section: Resultsmentioning
confidence: 99%
“…It is known that the resonances of hydrogen-bonded protons are shifted downfield relative to protons that are not involved in hydrogen bonds, thereby indicating that they are deshielded due to their participation in the hydrogen bonding. [37] A study on proton NMR spectroscopic shifts of these complexes indicated that C À H···N and amide hydrogen bonds also occur in solution in non-coordinating solvents (CDCl 3 and C 6 D 6 ). Table 1 shows the C À H and the aminopyridine N À H proton shifts, and the shift differences (Dd = 0.3-1.9 and 0.2-2.2 ppm) are largely attributable to aryl CÀH···N and NÀH···O=C hydrogen bonds in CDCl 3 , respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Ru(II)-based metallosurfactants, forming inverted aggregates, also have been reported . Furthermore, several calixarenes bearing long aliphatic chains form vesicles or micelles that can bind guest aromatic molecules …”
Section: Introductionmentioning
confidence: 94%
“…Modified crown ethers and aza crowns are compounds bearing various kinds and number of oxa, aza and thia heteroatom in their structures 8 . The second strategy for the modification of crown ethers and their derivatives is the synthesis of crown compounds with different structures, such as cryptands, calixarenes, lariats and biscrowns [9][10][11][12] .…”
Section: Introductionmentioning
confidence: 99%